Community-Based Interventions to Improve the Control of Non-Communicable Diseases in Underserved Rural Areas in Brazil: A Before-and-After Study - Lemos Macedo, Jéssica Caline; de Carvalho, Vivian Carla Honorato dos Santos; Cortes, Taciana Borges Andrade; Soares, Daniela Arruda; Mistro, Sóstenes; Kochergin, Clavdia Nicolaevna; Rumel, Davi; Oliveira, Marcio Galvão (Frontiers in Pharmacology, 2021)
Background: Hypertension and diabetes mellitus are the second and third highest leading causes of disability-adjusted life-years (DALY), respectively, in Brazil. The clinical outcomes of chronic diseases are influenced by various factors. Therefore, there is a need for multifaceted interventions to achieve a decrease in the rate of DALY, with a better control of these diseases. Objective: To verify whether sustainable long-term interventions, such as health worker training and provision of health education to the patients, contribute to health improvements in patients with hypertension and diabetes from rural communities. Methods: Over a 6-month period, educational and medical interventions were provided to optimize the treatment of hypertension and diabetes. Furthermore, blood pressure and glycated hemoglobin (HbA1c) measurements were taken at baseline and after the interventions. Results: The monitored hypertensive patients (n = 276) had a reduction of 13.4 mmHg (p = 0.021) and 5.8 mmHg (p <0.001) in mean systolic and diastolic blood pressure, respectively. Diabetic patients who were followed-up (n = 71) achieved a 0.55% (p = 0.185) reduction in HbA1c level. The desired blood pressure level (<140/90 mmHg) was achieved in 38.8% of patients with hypertension, whereas the desired level of HbA1c (<7.0% for adults and <8.0% for the elderly) was achieved in 16.9% of patients with diabetes; in addition, 38.0% had a reduction of HbA1c of at least 1%. Conclusions: The results showed that the interventions improved the blood pressure and HbA1c levels in patients with hypertension and diabetes from rural communities in a municipality in Northeast Brazil.